2007
DOI: 10.2967/jnumed.106.038596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Contrast-Enhanced MRI with 18F-FDG PET/201Tl SPECT in Dysfunctional Myocardium: Relation to Early Functional Outcome After Surgical Revascularization in Chronic Ischemic Heart Disease

Abstract: Revascularization of viable myocardial segments has been shown to improve left ventricular (LV) function and long-term prognosis; however, the surgical risk is comparatively higher in patients with a low ejection fraction (EF). We compared contrastenhanced MRI with 18 F-FDG PET/ 201 Tl SPECT for myocardial viability and prediction of early functional outcome in patients with chronic coronary artery disease (CAD). Methods: Forty-one patients with chronic CAD and LV dysfunction (mean age 6 SD, 66 6 10 y; 32 men;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 38 publications
1
30
1
2
Order By: Relevance
“…Recent studies have suggested that delayed enhancement (DE) on contrast-enhanced MRI represents irreversible myocardial injury. 52,53 There is limited information about the correlation between the presence of DE on MRI and acetate PET findings. Combined assessment of oxygen metabolism and tissue composition might be incrementally beneficial for predicting functional improvement after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that delayed enhancement (DE) on contrast-enhanced MRI represents irreversible myocardial injury. 52,53 There is limited information about the correlation between the presence of DE on MRI and acetate PET findings. Combined assessment of oxygen metabolism and tissue composition might be incrementally beneficial for predicting functional improvement after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate for individuals with undiagnosed myocardial infarction is significantly higher than that for diagnosed myocardial infarction (4). DE-MRI exhibits clear advantages in subendocardial myocardial infarction and small infarcts (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of viable myocardium assessed using gate-SPECT of myocardium ranging from 25 to 30 % of LV can be considered a reasonable cut-off value for a relatively accurate prediction of reverse LV remodeling onset (postoperative increase of LVEF >5 %) assessed using receiver operating curve (ROC) analysis 9 . To date, there is one study in which patients with substantial nonviable myocardium on 18 F-FDG/SPECT are predicted to have a poor early functional outcome 26 . Based on this fi nding we tested a fi xed perfusion defect parameter assessed using gated-SPECT of myocardium as a marker of a nonviable myocardial scar tissue in the light of reverse LV remodeling prediction defi ned as a simultaneous increase of LVEF of at least 5 % and decrease of EDV of at least 5 % evaluated after 11 months from revascularization, which we consider a long enough time interval for an onset of a functional recovery of hibernating regions of myocardium after coronary revascularization.…”
Section: Discussionmentioning
confidence: 99%